2016
DOI: 10.1097/icl.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Pathologic Myopia

Abstract: Pathologic myopia (PM) is one of the leading causes of visual impairment worldwide. The pathophysiology of PM is not fully understood, but the axial elongation of the eye followed by chorioretinal thinning is suggested as a key mechanism. Pathologic myopia may lead to many complications such as chorioretinal atrophy, foveoschisis, choroidal neovascularization, rhegmatogenous retinal detachment, cataract, and glaucoma. Some complications affect visual acuity significantly, showing poor visual prognosis. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 75 publications
(154 reference statements)
1
54
0
2
Order By: Relevance
“…1,2 Along with the increase in refractive error and axial length, highly myopic eyes frequently suffer from fundus vascular lesions such as macular hemorrhage and choroid neovascularization. 3,4 Previous studies have focused on the relationship between high myopia and large retinal vascular changes. Using color Doppler imaging, Benavente-Perez et al 5 demonstrated a pulse amplitude reduction in the central retinal artery of highly myopic eyes.…”
mentioning
confidence: 99%
“…1,2 Along with the increase in refractive error and axial length, highly myopic eyes frequently suffer from fundus vascular lesions such as macular hemorrhage and choroid neovascularization. 3,4 Previous studies have focused on the relationship between high myopia and large retinal vascular changes. Using color Doppler imaging, Benavente-Perez et al 5 demonstrated a pulse amplitude reduction in the central retinal artery of highly myopic eyes.…”
mentioning
confidence: 99%
“…Cho et al (2016) indicated that the point to practice guided discovery teaching with computer network technology was to provide interactive learning and induce intrinsic learning motivation. Learners proceeded independent or group operation activity in the interactive environment; the peer communication and feedback of operation experience allowed students' pleasant learning and learning achievement to enhance learning outcome.…”
Section: H2mentioning
confidence: 99%
“…Referring to Cho, Shin, and Yu (2016), the following dimensions are proposed for learning achievement in this study.…”
Section: Learning Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors include estrogen deficiency, taking corticosteroids, having certain eye conditions such as myopia, high blood pressure, diabetes, etc. [144][145][146][147][148]. Genetic studies of POAG have also identified multiple variants such as Gln368Ter in the MYOC gene which accounts for ~4% of all the POAG cases [149].…”
Section: Primary Open Angle Glaucoma and Age-related Macular Degeneramentioning
confidence: 99%